The use of analgesics and risk of self‐medication in an urban population sample: cross‐sectional study - Moreira de Barros, Guilherme Antonio [UNESP]; Calonego, Marco A. Marchetti [UNESP]; Mendes, Rannier F. [UNESP]; Castro, Raphael A.M. [UNESP]; Faria, João F.G. [UNESP]; Trivellato, Stella A. [UNESP]; Cavalcante, Rodney S. [UNESP]; Fukushima, Fernanda B. [UNESP]; Dias, Adriano [UNESP] (Elsevier, 2019)
Background and objectives: There are few data in the literature characterizing the pattern of analgesic use in Latin American countries, including Brazil. Little is known about the undertreatment of pain and its influence on the habit of self‐medication with analgesics. The aim of this study is to define the pattern of analgesic use among chronic pain patients and its potential association with self‐medication with analgesics. Method: Cross‐sectional observational study with an urban population sample. Chronic pain was defined as a pain lasting for at least 90 days. The study was approved by the Research Ethics Committee of the institution. Results: 416 subjects were included; 45.7% (n = 190) had chronic pain, with females (72.3%; p = 0.04) being the most affected. Self‐medication with analgesics is practiced by 78.4% of patients with chronic pain. The most common current analgesic treatment consists of non‐steroidal anti‐inflammatory drugs (dipyrone and acetaminophen). Weak opioids are rarely used and only 2.6% of subjects with chronic pain were taking these analgesics. None of the subjects were taking potent opioids. Conclusions: The practice of self‐medication with analgesics is frequent among patients with chronic pain, which may be due to the underprescription of more potent analgesics, such as opioids. It can also be said that, given the data presented, there is no crisis of recreational opioid use in the studied population.
Uso de analgésicos e o risco da automedicação em amostra de população urbana: estudo transversal
Keywords: Analgesics; Chronic pain; Self‐medication; Urban population